DEFINITION MATTERS: THE PITFALLS OF PROVERB STUDIES - Villers, Damien (Proverbium - Yearbook, 2024)
This article serves two main functions: it warns about the complexity and risks surrounding proverb definition and also offers solutions to increase insight and avoid pitfalls. The first part analyses the reasons for the absence of clear consensus among scholars and includes a summary of the main trends or views in specialised literature, as well as a “scale of consensus” for definition criteria. The second part advocates for an optimistic approach and a strict methodology to define proverbs, including several principles to boost legitimacy and bypass common obstacles. The final part showcases, through concrete examples, how terminology and proverb definition can influence or distort results in several fields of paremiology.